The Status of Muwa‘adah and Wa‘dan in the Syari‘ah - Abdullah, Md. Faruk; Ab Rahman, Asmak (Jurnal Fiqh, 2015)
This article discusses the Syari‘ah rulings for muwā‘adah and wa‘dān by reviewing the views of classical and contemporary scholars. It argues that muwā‘adah which is a mutual promise is different from a contract (‘aqd) even though the promise is binding on both parties. Therefore, it is allowed in the Syari‘ah to make a muwā‘adah for executing a sales contract (al-bay‘) on a future date. While a binding muwā‘adah is allowed in the Syari‘ah, it is more likely that wa‘dān which involves two independent promises should be permissible. A group of scholars however, does not allow muwā‘adah but this same group tolerate wa‘dān. Although binding muwā‘adah and wa‘dān are permissible in the Syari‘ah, their practices in some Islamic financial products involve certain conditions, and in some cases, their usage can be restricted based on sadd al-dharā’i‘ (blocking the means). This study is set benefit the Islamic finance industry with regards to developing products based on muwā‘adah and wa‘dān, while also encouraging academics to reconsider the Syari‘ah rulings for muwā‘adah.